(untitled) (Heritage, 2024)
Emerging technologies and the benefits they bring with them are increasingly entering every pore of society. A new trend combining virtual reality (VR) with the real-world scenarios, which is reflected in mixed reality (MR) devices, primarily in the HoloLens headset, which allows users to explore the mixed reality world and control their movements (even without using their hands), are increasingly finding their way to education sector. The subject of this paper is the analysis of the impact and advantages of mixed reality (MR) devices in education, with a special focus on building communication and student cooperation in the learning process. This paper aims to inform education experts about the advantages of integrating these new technologies into the classroom to boost student motivation, enhance students’ comprehension of the material being taught, and assist underachievers in overcoming obstacles to learning. The advent of immersive technologies has made it possible for students to learn remotely, which has shown to be very useful during the pandemic. Complex trainings, experiments, and group projects may now be conducted in virtual environment apart from reality, which can help students become more skilled and enthusiastic without worrying that the results will be less effective than they would be in a traditional setting.